Lee Clarson: capstone - Clarson, Lee, artist (Colorado State University. Libraries, 2024)
The artist's statement: My work focuses on the reflection of inner turmoil and the investigations for feeling in the 21st century. In contrast to written or spoken language, art holds a conversation with feelings like no other genre. You can explain in detail and pull metaphors left and right, but the intricacies of our feelings remain inescapable and unexpressed. Expressing myself and investigating my emotions through my art process supplies me with a method to work them out and understand myself better. It’s all too easy to be swept into the cycling thoughts of your mind, the worries that go unchecked and plans resculpted again and again. Talking or writing these out go ineffectual; more words to describe thoughts and ideas only complicate them further. Thus, my work represents these ideas better, working in abstract imagery while having a dialogue with myself. An important element of my art is investigating undefinable feelings or experiences and processing these until they’re tangible ideas and concepts represented in my work. My recent work is based in textile explorations and assemblage, examining the meaning of home and the various feelings that come with that idea. I'm interested in repetitive processes, such as mending and breaking and mending again, and interested in the ways these interactions connect to my feelings about the space I take in the world, connections to other people or my community, and the idea of home as a foundation for identity formation. These feelings are realized through thread stretched over layers of fabric, pieces cut out and rearranged to be sewn back together, and shredded tears dividing them once more. My work features bright colors and playful overlap while featuring rips, tears, and painstaking stitches. As a result, there’s a tension created between these differing feelings, reminiscent of playfulness whilst remaining tangled in the past.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: drawing